Urbanization and spatial connectivity in Ethiopia - Schmidt, Emily; Kedir Jemal, Mekamu (International Food Policy Research Institute, 2009)
This study uses Geographic Information Systems (GIS) techniques to estimate urbanization rates in Ethiopia, using a definition of urban extents that combines city population size, along with population density and travel times in surrounding areas. Defining the minimum population of an urban area as 50,000, the urbanization rate has risen from only 3.7 percent in 1984 to 14.2 percent in 2007. Over this same period, the percentage of the population more than 10 hours travel time from an urban center has fallen from 40.3 percent in 1984 to only 12.2 percent in 2007.